Accuracy of Ultrasound Scanning in Diagnosing Acute Appendicitis in Patients Admitted at Vicente Sotto Memorial Medical Center - Gurung, Uma; Gurung, Dhiraj (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Acute appendicitis is the most common abdominal surgical emergency. Both abdominal ultrasonography and computed tomography are common diagnostic tools in its diagnosis with each having its own advantages and disadvantages. Methods: Patients of suspected acute appendicitis were evaluated with an ultrasound to see the sensitivity, specificity, positive and negative predictive value of ultrasound for intraoperative appendicitis diagnosis. The study included 113 patients of suspected acute appendicitis presenting in the emergency during a one year duration. Sensitivity, specificity, positive predictive value and negative predictive value was calculated from their respective formulae. Results: The majority of the patients were male patients between the age group of 18 to 30. The sensitivity of ultrasound for diagnosis of acute appendicitis was 96% and specificity was 33%. The positive predictive value was 98% and the negative predictive value was 20% Conclusion: Ultrasound has good sensitivity and the low cost along with no radiation exposure makes this an acceptable screening investigative modality though due to low specificity, it would be recommended to go for a computed tomography scan if ultrasound shows negative result for appendicitis.